2013
DOI: 10.1017/s002531541300163x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in the foraging behaviour of the Galapagos sea lions (Zalophus wollebaeki) assessed using scat collections and stable isotope analysis

Abstract: This study focuses on the comparative analysis of variables related to the trophic niche plasticity in the Galapagos sea lion (Zalophus wollebaeki). There is great concern regarding the future of this species, so study of the diet and the way these animals obtain their food is useful to understand and predict their survival possibilities in the long term. The combined use of scat analysis and stable isotopes helps to determine foraging habits of this species in greater detail. The objective of the study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 44 publications
(73 reference statements)
4
40
0
Order By: Relevance
“…The marine habitat characteristics and the environmental conditions, which differ in each region of the Galapagos Archipelago [36], influence the habitat use of the GSL [8,1517] and determine the population trend of its rookeries; thus, similar population trends were expected among spatially close rookeries in the same region. However, we found different abundance patterns among rookeries in the SER, suggesting that the population trend of a single rookery should not be considered representative of the trend in the entire region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The marine habitat characteristics and the environmental conditions, which differ in each region of the Galapagos Archipelago [36], influence the habitat use of the GSL [8,1517] and determine the population trend of its rookeries; thus, similar population trends were expected among spatially close rookeries in the same region. However, we found different abundance patterns among rookeries in the SER, suggesting that the population trend of a single rookery should not be considered representative of the trend in the entire region.…”
Section: Discussionmentioning
confidence: 99%
“…that alternate in frequency and abundance between the seasons [8,46]. This flexibility in the foraging behavior of the GSL has enabled it to adapt to the changing conditions of the Galapagos ecosystem and may thereby improve its survival [15]. …”
Section: Discussionmentioning
confidence: 99%
“…However, satellite telemetry studies suggest the presence of two feeding strategies (pelagic and benthic), which could expand the trophic niche of this species given the region's environmental variability and the competition with other predators . This type of behavior has been related to a strategy by Z. wollebaeki to avoid competition with A. galapagoensis , primarily during the warmest months of the year when there is less prey available …”
Section: Discussionmentioning
confidence: 99%
“…The feeding habits of the Galapagos pinnipeds have been moderately studied using mainly scat analysis . However, this technique incurs intrinsic temporal biases since it provides a single snapshot of the diet of each individual before sampling, which necessitates the use of complementary techniques …”
mentioning
confidence: 99%
“…Using scats and stable isotope analysis, Páez-Rosas & Aurioles- Gamboa (2014) found that despite stability in trophic level, the diet of Galapagos sea lions, Zalophus californianus wollebaeki, was variable in space and time, which likely helps the species survive in an ecosystem with limited and fluctuating resources.…”
mentioning
confidence: 99%